2014
DOI: 10.3109/0886022x.2014.915196
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in renal transplant recipients with lupus nephritis: experience at a single center

Abstract: Background: The long-term prognosis of renal transplant recipients with systemic lupus erythematosus is still controversial. The outcome of these patients depends on the population studied, race/ethnicity, socioeconomic conditions, donor-related factors and recurrent lupus nephritis (LN), among other factors. Objective: This study was conducted to evaluate kidney transplantation outcomes for adult Brazilian patients with LN at a single center. Subjects and method: The archival records of all patients with LN w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
4
8
1
Order By: Relevance
“…The long-term prognosis of renal transplantation patients with SLE is a matter of controversy, but some studies have shown patient survival to be similar in graft recipients with and without SLE 6,1720 . During the 5-year follow-up period of this study, only 5.3% died, matching findings in the literature, including the three Brazilian studies evaluating renal transplantation patients with SLE and LN 810,21 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The long-term prognosis of renal transplantation patients with SLE is a matter of controversy, but some studies have shown patient survival to be similar in graft recipients with and without SLE 6,1720 . During the 5-year follow-up period of this study, only 5.3% died, matching findings in the literature, including the three Brazilian studies evaluating renal transplantation patients with SLE and LN 810,21 .…”
Section: Discussionsupporting
confidence: 88%
“…In this study we evaluated the clinical and epidemiological characteristics, graft survival time, patient survival and its determinants, and recurrence of SLE in a cohort of LN patients submitted to renal transplantation at our institution between 1996 and 2016, and compared our findings with the national and international literature. To our knowledge, only three other studies on renal transplantation patients with SLE and LN have been conducted in Brazil 810 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed SLE adversely affects the transplant outcome, (8-10) whilst others did not support this. [11][12][13][14][15][16] The largest retrospective study usingUnited StatesRenalData System (USRD) and United Network for Organ Sharing(UNOS) databases showed transplantation in SLE had inferior graft and recipient outcome compared with diabetic ESRD patients. 17 One important consideration regarding SLE is that it might create obstacle from getting CDC cross-match negative donor and render them on long waiting list 18 as in this case, which would have definite adverse prognostic impact on transplant outcome.…”
Section: Discussion Of the Casementioning
confidence: 99%